PENINGKATAN KECERDASAN MUSIKAL ANAK USIA 5-6 TAHUN MELALUI PERMAINAN GAMELAN MINI DI TK ARSYAKA KOTA BENGKULU - Aditia, Dela Laras; Agustina, Aisya; Putri, Shela Ramadhan; Sapitri, Zelvi; Budrianto (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Tearly childhood education is an important stage in developing children's potential and multiple intelligences, including musical intelligence. Based on observations conducted at TK Arsyaka Bengkulu City, the musical intelligence of children aged 5–6 years still needs to be enhanced through engaging learning activities that suit their developmental characteristics. On the other hand, the school possesses valuable assets such as supportive teachers, a conducive learning environment, and learning media that can be utilized to foster children's musical abilities. This program aimed to determine the implementation of mini gamelan games in improving the musical intelligence of children aged 5–6 years at TK Arsyaka Bengkulu City. The method applied was the Asset Based Community Development (ABCD) approach, consisting of Discovery, Dream, Design, and Destiny stages. The results showed that the implementation of mini gamelan games successfully improved children's musical intelligence, as indicated by their increased ability to recognize rhythms, follow tempo, distinguish sounds, and play simple musical instruments. In addition, children demonstrated greater enthusiasm and active participation during learning activities. The Societal Impact Index also indicated a very high level of satisfaction among teachers and parents regarding the program implementation. Therefore, mini gamelan games can serve as an effective learning medium for enhancing musical intelligence in early childhood while creating positive impacts within the school community.